Genetic engineering a large animal model of human hypophosphatasia in sheep. Issue 1 (December 2018) - Williams, Diarra; Pinzón, Carlos; Huggins, Shannon; Pryor, Jane; Falck, Alyssa; Herman, Forrest; Oldeschulte, James; Chavez, Michael; Foster, Brian; White, Sarah; Westhusin, Mark; Suva, Larry; et al.
Abstract The availability of tools to accurately replicate the clinical phenotype of rare human diseases is a key step toward improved understanding of disease progression and the development of more effective therapeutics. We successfully generated the first large animal model of a rare human bone disease, hypophosphatasia (HPP) using CRISPR/Cas9 to introduce a single point mutation in the tissue nonspecific alkaline phosphatase (TNSALP) gene (ALPL ) (1077 C > G) in sheep. HPP is a rare inherited disorder of mineral metabolism that affects bone and tooth development, and is associated with muscle weakness. Compared to wild-type (WT) controls, HPP sheep have reduced serum alkaline phosphatase activity, decreased tail vertebral bone size, and metaphyseal flaring, consistent with the mineralization deficits observed in human HPP patients. Computed tomography revealed short roots and thin dentin in incisors, and reduced mandibular bone in HPP vs. WT sheep, accurately replicating odonto-HPP. Skeletal muscle biopsies revealed aberrant fiber size and disorganized mitochondrial cristae structure in HPP vs. WT sheep. These genetically engineered sheep accurately phenocopy human HPP and provide a novel large animal platform for the longitudinal study of HPP progression, as well as other rare human bone diseases.